2022
DOI: 10.1002/clc.23829
|View full text |Cite
|
Sign up to set email alerts
|

The association between systemic inflammatory response index and in‐hospital mortality in patients with infective endocarditis

Abstract: Background Infective endocarditis (IE) has a significant mortality, and early identification of high‐risk patients and prediction of poor outcomes is of great significance. In recent years, increasing research has revealed the predictors associated with infective endocarditis prognosis. Systemic inflammatory response index (SIRI) is an important new indicator of inflammation. So far, there have been no reports on the relationship between SIRI and the prognosis of IE patients. Hypothesis The purpose of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“… 4 In addition, SIRI was shown to be associated with C-reactive protein (CRP) levels, suggesting that SIRI is an indicator of inflammation levels in the body. 31 , 34 It has also been verified that SIRI was relatively more stable than CRP, as the latter parameter had a greater risk of being impacted by blood specimen handling techniques and other infectious diseases. 35 Our study also found that patients with higher SIRI levels had a greater risk of long-term clinical cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“… 4 In addition, SIRI was shown to be associated with C-reactive protein (CRP) levels, suggesting that SIRI is an indicator of inflammation levels in the body. 31 , 34 It has also been verified that SIRI was relatively more stable than CRP, as the latter parameter had a greater risk of being impacted by blood specimen handling techniques and other infectious diseases. 35 Our study also found that patients with higher SIRI levels had a greater risk of long-term clinical cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 98%
“… 30 These composite indicators are more stable and less susceptible than a single inflammatory indicator. 31 Previous studies have shown that SIRI is a predictor of prognosis in various types of cancer. 32 Very few studies have evaluated its association with patients with ACS after PCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3] Studies have shown that prognostic inflammatory index (PII) and systemic inflammatory response index (SIRI) are new indicators for evaluating systemic inflammation, nutrition, and immune status; which have been used in the diagnosis and prognosis of cancer and infectious diseases, such as breast cancer, gastric cancer, rectal cancer, and infective endocarditis. [6][7][8][9] PII and SIRI are calculated according to the laboratory indicators of patients during hospitalization, which has the added advantages of simplicity and convenience. [6,10] Pathological changes in pulmonary TB mainly include inflammatory exudation, hyperplasia, and caseous necrosis.…”
Section: Introductionmentioning
confidence: 99%